Farmers' farmland quality protection behavior: influencing factors and policy implications in eastern coastal China - Ye, Nannan; Xu, Yan; Zhang, Runsen (Frontiers in Sustainable Resource Management, 2025)
IntroductionFarmers' farmland quality protection behavior (FQPB) is influenced by many factors, which, by shaping decision-making processes of farmers impact the maintenance and enhancement of farmland quality.MethodsIn this study, the factors influencing FQPB in Yancheng Prefecture, in a typical area of Jiangsu Province, were explored using survey data of 190 farmers. The mechanisms underlying the influence of farmland utilization dynamics, agricultural production costs, agricultural machinery resource dynamics, family land resources, and agricultural cultivation patterns on FQPB were empirically tested using structural equation modeling.ResultsWe found a significant inhibitory effect of farmland use dynamics on FQPB. The greatest effects were those related to farmland transfer and the proportion of transferred farmland. Agricultural machinery resource dynamics, and specifically, the use and the degree of ownership of agricultural machinery and equipment, were also identified as having a significant effect on FQPB. The significant contribution of the agricultural cropping pattern on FQPB included total cropping type, non-food crop cropping, and non-food crop type.DiscussionFindings from this study reaffirm that policies promoting moderate farmland transfer and encouraging food crop cultivation may enhance farmers' motivation to engage in farmland quality protection. Enhancing agricultural extension services may also strengthen farmers' willingness to participate in farmland quality protection.